Human : the science behind what makes us unique - Gazzaniga, Michael S. (New York : Ecco, 2008)
One of the world's leading neuroscientists explores how best to understand the human condition by examining the biological, psychological, and highly social nature of our species within the social context of our lives. In Human, Gazzaniga explores a number of related issues, including what makes human brains unique, the importance of language and art in defining the human condition, the nature of human consciousness, and even artificial intelligence.
The basics of human life: Are human brains unique? -- Would a chimp make a good date? -- Navigating the social world: Big brains and expanding social relationships -- The moral compass within -- I feel your pain -- The glory of being human: What's up with the arts? -- We all act like dualists: the converter function -- Is anybody there? -- Beyond current constraints: Who needs flesh?
Includes bibliographical references (p. [391]-431) and index.
Keywords: Cognitive neuroscience; Neuropsychology; Human beings; Consciousness